Counting coconuts with drones - Reynolds, Ephraim; Felolini Tafuna'I, Faumuina (Technical Centre for Agricultural and Rural Cooperation, 2016)
On the Pacific islands of Samoa drone technology is used in a coconut tree survey to forecast more accurately yield and production of virgin coconut oil.